Assessment of the knowledge of dental students on biosafety (Research, Society and Development, 2022)
Dental surgery is exposed to a wide variety of microorganisms, due to the flow of care, which can be different from an infectious disease, without developing the disease and presenting the symptoms and symptoms of the disease. Thus, a potential chain of cross-infection is installed, from one patient to another for the professional himself and his work team. Thus, the aim of this study was to evaluate the knowledge and conduct of dentistry studies in relation to biosafety. Thus, the students of a Dentistry question from the São Paulo survey who agreed to build a Faculty of Dentistry built 18 questions. Observing 15367 (%) of the studies that never participated in the event with the theme that they never had knowledge about safety, 157 (6%) thought they had knowledge about cross-infection. When asked if they knew what personal protective equipment and collective protective equipment are, most answered yes. In matters of safe conduct issues that address the security relationship of the updated business portfolio 93.8% (212) In relation to an exchange of all mechanics in the care of each patient 87.2% of the costs (197) of the calculations of comparison of all necessary exchange. In the operation of the prewash, mechanical washing, disinfection and sterilization steps were identified printing and handling. It was concluded that the security services, showed knowledge about bio-infection, note the steps of infection control of the instrument.